Who Saves in Ireland? : The Micro Evidence - Moreno Badia, Marialuz (Washington, D.C. : International Monetary Fund, 2006)
This paper provides detailed empirical evidence on the saving behavior of Irish households using micro data from the 1994/95 and 1999/2000 Household Budget Surveys. I employ synthetic cohort techniques to characterize the life cycle profile of saving rates and to examine the response of household saving to house price appreciation. The analysis suggests that households at the peak of their working lives have relatively low savings though there is no evidence of a generational savings gap. Also, despite housing being a major component of Irish households, wealth, there is no strong relationship between savings and housing capital gains.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet